FutureLight: Lampu Taman Berbasis IoT dengan Sumber Energi Terbarukan - Sinaga, Pratama Anggi Kurnia; Kiswantono, Agus (INTER TECH, 2025)
This research explores the design and development of the Smart Solar Cell Lamp an environmentally friendly garden lighting system that runs on renewable energy. The lamp is powered through a hybrid system that combines solar panels as the main energy source with a PLN (state electricity) adapter as a backup, allowing it to operate reliably even when sunlight is limited. To make the system more efficient, an LDR (Light Dependent Resistor) sensor is used to automatically adjust the LED brightness according to the surrounding light conditions. The research applies a prototype approach, starting from identifying the core problem to designing, assembling, and testing the device. Test results show the solar panel consistently generates voltage between 15.69 V and 16.49 V, with the battery storing up to 13.30 V. During nighttime operation, the system maintains a steady supply of current and voltage to power the LEDs. The LDR sensor responds well to changes in ambient light, allowing the lamp to switch on and off automatically without user input. While the system performed as expected under lab conditions, further improvements such as better weather protection, enhanced durability, and remote monitoring are recommended to support long-term use and real-world deployment